2017
DOI: 10.1080/19336950.2017.1279368
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of intracellular transport in TREK-1c current run-up in 293T cells

Abstract: The TREK-1 channel, the TWIK-1-related potassium (K+) channel, is a member of a family of 2-pore-domain K+ (K2P) channels, through which background or leak K+ currents occur. An interesting feature of the TREK-1 channel is the run-up of current: i.e. the current through TREK-1 channels spontaneously increases within several minutes of the formation of the whole-cell configuration. To investigate whether intracellular transport is involved in the run-up, we established 293T cell lines stably expressing the TREK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Immediately after whole-cell access, small outward currents were recorded in response to depolarizing step pulses ( Fig 1A , 0 min). As reported previously [ 21 ], the channel current exhibited a gradual and spontaneous increase, which is called run-up, and reached a maximum level 3 min after establishing the whole-cell access. After the end of run-up (5 min), the current amplitude was the same as at 3 min ( Fig 1A and 1C ).…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Immediately after whole-cell access, small outward currents were recorded in response to depolarizing step pulses ( Fig 1A , 0 min). As reported previously [ 21 ], the channel current exhibited a gradual and spontaneous increase, which is called run-up, and reached a maximum level 3 min after establishing the whole-cell access. After the end of run-up (5 min), the current amplitude was the same as at 3 min ( Fig 1A and 1C ).…”
Section: Resultssupporting
confidence: 71%
“…We previously prepared a lentiviral vector that expressed the TREK-1 channel [ 16 ] and using this vector we established a cell line, TR-1, which stably expressed the channel [ 21 ]. First, we confirmed the expression of the channel current in this cell line with whole cell patch-clamp recordings.…”
Section: Resultsmentioning
confidence: 99%
“…Over recovery from inhibition was also lost in the shortest isoform of TREK-2 suggesting that the N terminus of the channel is also important for recovery of channel activity following application of sipatrigine. In TREK-1 channels, the N terminus interacts with the protein EBP50 in the plasma membrane which stabilises the structure of proteins and leads to a gradual run-up of current in the whole-cell configuration [ 30 ]. Therefore, loss of this interaction in the short form of TREK channels, may lead to a change in compound effects on the channel.…”
Section: Resultsmentioning
confidence: 99%
“…The membrane localization of several adhesion receptors, such as ICAMs, CD43, and CD44, were regulated by cytoskeleton through one or more members of the ezrin, radixin, and moesin (ERM) family of proteins [47]. The TREK-1 channel was previously found to co-localize with ezrin and induce the formation of actin-rich protrusions [48]. Bittner et al have found these adhesion molecules play a role in the TREK-1 deficiency-mediated immune infiltration in mice EAE model [18].…”
Section: Discussionmentioning
confidence: 99%